Effect of robotic exoskeleton training on lower limb function, activity and participation in stroke patients: a systematic review and meta-analysis of randomized controlled trials - Yang, Juncong; Zhu, Yongxin; Li, Haojie; Wang, Kun; Li, Dan; Qi, Qi (Frontiers in Neurology, 2024)
Background The current lower limb robotic exoskeleton training (LRET) for treating and managing stroke patients remains a huge challenge. Comprehensive ICF analysis and informative treatment options are needed. This review aims to analyze LRET’ s efficacy for stroke patients, based on ICF, and explore the impact of intervention intensities, devices, and stroke phases. Methods We searched Web of Science, PubMed, and The Cochrane Library for RCTs on LRET for stroke patients. Two authors reviewed studies, extracted data, and assessed quality and bias. Standardized protocols were used. PEDro and ROB2 were employed for quality assessment. All analyses were done with RevMan 5.4. Results Thirty-four randomized controlled trials (1,166 participants) were included. For function, LRET significantly improved motor control (MD = 1.15, 95%CI = 0.29–2.01, p = 0.009, FMA-LE), and gait parameters (MD = 0.09, 95%CI = 0.03–0.16, p = 0.004, Instrumented Gait Velocity; MD = 0.06, 95%CI = 0.02–0.09, p = 0.002, Step length; MD = 4.48, 95%CI = 0.32–8.65, p = 0.04, Cadence) compared with conventional rehabilitation. For activity, LRET significantly improved walking independence (MD = 0.25, 95%CI = 0.02–0.48, p = 0.03, FAC), Gait Velocity (MD = 0.07, 95%CI = 0.03–0.11, p = 0.001) and balance (MD = 2.34, 95%CI = 0.21–4.47, p = 0.03, BBS). For participation, social participation (MD = 0.12, 95%CI = 0.03–0.21, p = 0.01, EQ-5D) was superior to conventional rehabilitation. Based on subgroup analyses, LRET improved motor control (MD = 1.37, 95%CI = 0.47–2.27, p = 0.003, FMA-LE), gait parameters (MD = 0.08, 95%CI = 0.02–0.14, p = 0.006, Step length), Gait Velocity (MD = 0.11, 95%CI = 0.03–0.19, p = 0.005) and activities of daily living (MD = 2.77, 95%CI = 1.37–4.16, p = 0.0001, BI) for the subacute patients, while no significant improvement for the chronic patients. For exoskeleton devices, treadmill-based exoskeletons showed significant superiority for balance (MD = 4.81, 95%CI = 3.10–6.52, p < 0.00001, BBS) and activities of daily living (MD = 2.67, 95%CI = 1.25–4.09, p = 0.00002, BI), while Over-ground exoskeletons was more effective for gait parameters (MD = 0.05, 95%CI = 0.02–0.08, p = 0.0009, Step length; MD = 6.60, 95%CI = 2.06–11.15, p = 0.004, Cadence) and walking independence (MD = 0.29, 95%CI = 0.14–0.44, p = 0.0002, FAC). Depending on the training regimen, better results may be achieved with daily training intensities of 45–60 min and weekly training intensities of 3 h or more. Conclusion These findings offer insights for healthcare professionals to make effective LRET choices based on stroke patient needs though uncertainties remain. Particularly, the assessment of ICF participation levels and the design of time-intensive training deserve further study. Systematic review registration https://www.crd.york.ac.uk/PROSPERO, Unique Identifier: CRD42024501750.